2004
DOI: 10.1097/01.nmd.0000144695.02982.41
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Social Support, and Posttraumatic Stress in Postwar Kosovo

Abstract: The effects of social support and traumatic experiences on mental health in conflict situations may be different by gender. The Kosovo Emergency Department Study was conducted in July and August 2001 to assess mental health 2 years after the end of the war in Kosovo. Of 306 emergency department patients (87.7% response rate), all were ethnic Albanian, 97.4% had experienced traumatic events, and 89.5% had posttraumatic stress symptoms. Women and persons who experienced more traumatic events had higher posttraum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 37 publications
(93 reference statements)
7
83
0
Order By: Relevance
“…Females scored exceptionally high for PTSD (32.6%) compared to males (15.2%). Female risk factors have been widely documented in the literature contributing to a higher vulnerability for mental health related disorders following trauma exposure [2,11,20,49,54]. In a meta-analysis of risk factors for PTSD in adults exposed to trauma, Brewin et al [11] found that risks included female gender, education level, previous trauma, psychiatric history, age of trauma, and race with effect sizes of factors becoming stronger after a traumatic event, such as, severity of trauma, lack of social support and additional life stressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females scored exceptionally high for PTSD (32.6%) compared to males (15.2%). Female risk factors have been widely documented in the literature contributing to a higher vulnerability for mental health related disorders following trauma exposure [2,11,20,49,54]. In a meta-analysis of risk factors for PTSD in adults exposed to trauma, Brewin et al [11] found that risks included female gender, education level, previous trauma, psychiatric history, age of trauma, and race with effect sizes of factors becoming stronger after a traumatic event, such as, severity of trauma, lack of social support and additional life stressors.…”
Section: Discussionmentioning
confidence: 99%
“…check points, curfews, instability in flow of goods and services) could have also put females at further risk of having high PTSD thresholds. Social support has been found to be a major protective factor against PTSD symptoms in trauma-exposed females [2]. Further research is needed to identify risk status and enhancing protective factors in female civilian populations residing in high conflict areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, females may experience greater objective exposure, may have greater prior trauma, or may have a greater number of postdisaster stressors (Kimerling, Mack, & Alvarez, 2009). Note, however, in multivariate models that controlled for possible confounds of this nature, female gender was still found to predict both greater disaster-related psychopathology (Ahern, Galea, Fernandez, et al, 2004;Hoven et al, 2005;Galea, Tracy, Norris, & Coffey, 2008;Weems et al, 2010) and reduced resilience Bonanno, Galea, et al, 2007).…”
Section: The Predisaster Contextmentioning
confidence: 93%
“…Nearly 16 years after the 1998-1999 war, which had left a large part of the population with mood disorders (47.6%) and anxiety (41.8%; Priebe et al, 2010), a number of studies were conducted in Kosovo on post-traumatic stress in war victims. Those studies were focused on hospitalized persons (Ahern et al, 2004), relatives of the victims (Morina, Rudari, Bleichhardt, & Prigerson, 2010), victims of torture (Wang et al, 2012), refugees (Ai, Peterson, & Ubelhor, 2002), and adolescents (Gordon, Staples, Blyta, Bytyqi, & Wilson, 2008).…”
Section: Introductionmentioning
confidence: 99%